PERAN HUKUM ADAT DAYAK BAKATI DALAM MEMBENTUK CIVIC VIRTUE MASYARAKAT DESA SEKARUH KECAMATAN TERIAK KABUPATEN BENGKAYANG - Merry Krisdayanti; Endang Susilowati; Thomy Sastra Atmaja (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThe title research is "Role of Dayak Bakati Customary Law in forming the Civic Virtue of theSekaruh Village Community, Shouts District, Bengkayang Regency". The purpose of this study wasto determine clearly the role of Dayak bakati customary law in forming the civic virtue of thepeople of Sekaruh Village, Shouts District, Bengkayang Regency. The research method used is aqualitative research method with a descriptive type of research. The sources in this study are thecommunity (adolescents, adults, and the elderly) in Sekaruh Village. Data collection techniques t ,through observation, interviews, and documentation, the data collection tools are interview guides,observation guides and documentation tools. The analysis in this study was presented in aqualitative descriptive manner, using 8 informants namely traditional leaders, village heads andthe community (adolescents, adults, and parents). Results of the papers this (1) The formscustomary law in Sekaruh Village are fighting, taking someone's wife/husband, impregnatingsomeone's child and not wanting to be responsible, stealing, murdering/killing, throwing awaywife/husband (divorce), sexual harassment, land boundary disputes. , domestic violence and others.(2) the role of customary law, namely as a means to protetc the community, creating communitybalance, give a taste justice, comfort, and peace in society, fostering a sense of responsibility forviolators of customary law who have been sanctioned, then can foster a sense of tolerance in eachindividual. (3) Impact customary law on the formation civic virtue is that people's behaviorbecomes orderly, obeys the law, fosters a sense of love for local culture, provides a deterrent effect,decreases criminal and civil actions, shapes the character of all levels of society (teenagers, adultsand parents) to become directed and civilized so as to form the civic virtue of society.Keywords: Customary Law, Civic Virtue, Society